A 10‐year review of surgical management of dermatofibrosarcoma protuberans. (1st April 2021) - Durack, A.; Gran, S.; Gardiner, M.D.; Jain, A.; Craythorne, E.; Proby, C.M.; Marsden, J.; Harwood, C.A.; Matin, R.N.; ,; Affleck, A; Ahmed, A; et al.
Summary: Background: Dermatofibrosarcoma protuberans (DFSP) is a rare skin cancer. Standard treatment in the UK is either wide local excision (WLE) or Mohs micrographic surgery (MMS). It is unclear which approach has the lower recurrence rate. Objectives: We undertook a retrospective comparative review of surgical management of DFSP in the UK National Health Service in order to define (i) current surgical practice for primary and recurrent DFSP, (ii) local recurrence rates for primary DFSP and (iii) survival outcomes for DFSP. Methods: A retrospective clinical case‐note review of patients with histologically confirmed DFSP (January 2004 to December 2013) who have undergone surgical treatment. Results: The surgical management of 483 primary and 64 recurrent DFSP in 11 plastic surgery and 15 dermatology departments was analysed. Almost 75% of primary DFSP ( n = 362) were treated with WLE and 20% ( n = 97) with MMS. For recurrent DFSP, 69% ( n = 44) and 23% ( n = 15) of patients underwent WLE and MMS, respectively. Recurrent primary DFSP occurred in six patients after WLE and none after MMS. The median follow‐up time was 25·5 months (interquartile range 6·8–45·1) for new and 19·8 (IQR 4·5–44·5) for recurrent DFSP [Correction added on 1 Feb 2021, after first online publication: 4.8 years (interquartile range 3.5‐5.8) was incorrect], with eight reported deaths during the follow‐up analysis period (one confirmed to be DFSP related). Conclusions: WLE was the most common surgical modality used to treat DFSP across the UK. The local recurrence rate was very low, occurring only after WLE. Although a prospective randomized controlled trial may provide more definitive outcomes, in the absence of a clearly superior surgical modality, treatment decisions should be based on patient preference, clinical expertise and cost.